UPAYA GURU PAI DALAM PEMBENTUKAN KARAKTER PEDULI LINGKUNGAN DI SEKOLAH - Subhi Nur Ishaki; Qonita; Zahara; Junaidah; Chairul Amriyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The focus of this research is on how Islamic religious teachers can implement environmental awareness attitudes at Madrasah Tsanawiyah Nurul Falah Tanjung Baru Merbabu Mataram, South Lampung using a qualitative case study approach. Primary data consists of: teachers, students, and school administrators. In this research, interview, observation, and documentation techniques were used to collect data. Furthermore, the author uses data triangulation techniques to ensure that the data is accurate. The results of this study indicate that maintaining environmental cleanliness at MTs Nurul Falah involves various programs and activities designed to increase the awareness and participation of students, teachers, and the community. Programs such as tree planting, daily and monthly cleanliness systems, and recycling education have shown positive results in increasing students' awareness of the importance of maintaining cleanliness and environmental sustainability. However, several challenges still need to be addressed, including the lack of separation between the school and the surrounding environment, the absence of a canteen, low student awareness, limited cleanliness facilities, and inconsistent supervision.